A Correlation Between Education, Occupation And Socio-Economic Levels With Selection Of Contraceptive Methods In Feertile Age Couples At Bangun Jaya Helath Center In 2024 - Royani, Tutik; Umami, Desi Aulia; Putri, Yesi (Student Scientific Journal, 2025)
According to Worldometers data in March 2020, Indonesia's population was 273,523,615 people with a population density of 151 people per km2, this number tends to increase compared to 2019, which was 270,625,568 people. The purpose of the study is to determine a correlation between education, employment and socio-economic levels with the selection of contraceptive methods in fertile age couples at Bangun Jaya Health Center in 2024. This study uses analytic research with cross sectional design. Sampling with nonprobability sampling method with purposive sampling technique, namely sampling based on researcher judgment and in accordance with the inclusion and exclusion criteria. Sampling with a total of 90 people. Chi-square test results show that the variable level of education, with the selection of contraceptive methods in fertile age couples with chi-square p-value of 0.001 (α <0.05), work with the selection of contraceptive methods in fertile age couples with a chi-square p-value of 0.001 (α <0.05), social economy with the selection of contraceptive methods in fertile age couples with the results of chi-square p-value 0.001 (α <0.05) so it can be concluded that there is a correlation between education level, occupation and social economy with the selection of contraceptive methods in fertile age couples at Bangun Jaya Health Center in 2024. It is recommended that the Health Center as a further reference to deal with the selection of contraceptive methods in fertile age couples.